2015
DOI: 10.12816/0024924
|View full text |Cite
|
Sign up to set email alerts
|

Presepsin as a Novel Diagnostic Marker in Neonatal Septicemia

Abstract: Background: Neonatal septicemia is a serious life-threatening condition with high mortality. The accurate diagnosis of sepsis is one of the main challenges in emergency medicine. A great effort to reduce the neonatal mortality rate is put into looking for new reliable biomarkers. Among biomarkers, presepsin could be one of the most promising and reliable biomarker for early diagnosis of sepsis. Objective: We aimed to evaluate the diagnostic value of presepsin in the early diagnosis of neonatal sepsis. Methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…This was in agreement with the studies of De Benedetti et al and Dzwonek et al, in which nearly half of the positive blood cultures grew K. pneumonia 20,21. On the contrary, Osman et al demonstrated that the most common isolated organism from septic neonates was coagulase-negative Staphylococci (17.5%) followed by Staphylococcus aureus (12.5%) and K. pneumonia (10%) 22. This difference may be attributed to variation in local epidemiology and the microbial etiology of sepsis in addition to different care practices between medical centers.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This was in agreement with the studies of De Benedetti et al and Dzwonek et al, in which nearly half of the positive blood cultures grew K. pneumonia 20,21. On the contrary, Osman et al demonstrated that the most common isolated organism from septic neonates was coagulase-negative Staphylococci (17.5%) followed by Staphylococcus aureus (12.5%) and K. pneumonia (10%) 22. This difference may be attributed to variation in local epidemiology and the microbial etiology of sepsis in addition to different care practices between medical centers.…”
Section: Discussionsupporting
confidence: 90%
“…However, due to the lack of information about presepsin reference range in neonates, many studies reported different cut-off values 22,25,26. Relatively different cut-off values may be due to the use of different measurement methods.…”
Section: Discussionmentioning
confidence: 99%
“…Out of those five articles, one article was not available in full text [24] and two other articles were not eligible for our review (in one article it was unclear whether they investigated EOS or LOS [25] and in one article unusual ranges of sCD14-ST values were used [26]). Therefore out of this review, two articles [27, 28] were found to be appropriate to use in our review and were included afterwards. The literature search is summarized in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In total 12 studies were included for qualitative synthesis in this systematic review. An overview of the characteristics of these studies is shown in Table 1 [913, 27–33]. All included studies were prospective observational studies and studied septic and healthy neonates.…”
Section: Resultsmentioning
confidence: 99%
“…We determined low cut off levels and weak specificity and PPV in contrast to good sensitivity and high NPV. There are only few existing paediatric studies focused on analysis of presepsin's diagnostic usefulness, mainly in newborns [18,21]. Papers considered febrile episodes in childhood oncology patients reported also inconclusive results [17,20].…”
Section: Discussionmentioning
confidence: 99%